Analisis Perkembangan Teknologi Digital dalam Keagenan Pelayanan Kapal Di PT. Seroja Jaya Agensi Palembang - Santiara Salsabila Haryadi; Sarifuddin; Muhammad Syukri (PPPM - POLITEKNIK PELAYARAN SURABAYA, 2025)
This study examines the implementation of digital technology in ship agency operations at PT. Seroja Jaya Agensi, Palembang Branch, to improve operational efficiency in the digital transformation era. A qualitative method was employed through interviews, observations, and document analysis. Findings reveal that digital systems such as INAPORTNET, INSW, PHINISI, and SINKARKES enhance service speed, document accuracy, and human resource utilization. Challenges include infrastructure limitations, data entry errors, and cybersecurity threats. The study highlights the need for employee training and robust information security policies. It concludes that digitalization positively impacts company performance and supports the sustainability of the maritime sector. A collaborative and strategic approach to digital adoption is essential to address the evolving demands of the maritime industry.